Dominican Republic Tax System Review - World Bank (World Bank, Washington, DC, 2021)
Despite decades of impressive economic growth, tax revenues in the Dominican Republic (DR) remain well below the regional average. The DR’s tax base is extremely narrow, with extensive exemptions, deductions, zero-ratings, and allowances across all major tax categories. Tax expenditures amounted to an estimated 4.8 percent of gross domestic product (GDP) in 2020, of which value-added tax (VAT) exemptions alone accounted for 2.5 percentage points. High levels of tax noncompliance and low tax morale further diminish revenue collection. An excessively complex and overly generous array of tax incentives weakens the performance of corporate income tax (CIT) while doing little to advance the government’s economic development objectives. A high eligibility threshold and various exemptions narrow the personal income tax (PIT) tax base. Tax reforms should be phased in over time with broad public support. In the current macroeconomic climate, the sudden withdrawal of the debt-financed fiscal stimulus will have deeply negative repercussions. Tax reform is subject to a variety of political, economic, and administrative challenges that must be addressed as part of a broader fiscal strategy that provides predictability to the private sector and enjoys substantial public support. In parallel, the government must ensure that it has adequate administrative capacity to offset the impact of measures that may adversely affect poor and vulnerable households. The government’s fiscal strategy should reflect the lessons of the international experience, and it should be informed by a thorough and detailed analysis of the economic and distributional implications of tax reform.